2020
DOI: 10.3390/polym12030538
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biocompatibility of Multi-Layered, 3D Bio-Printed Artificial Vessels Composed of Autologous Mesenchymal Stem Cells

Abstract: Artificial vessels capable of long-term patency are essential clinical tools in vascular surgery that involves small vessels. On-going attempts to develop artificial vessels that complements restenosis have not been entirely successful. Here, we report on the fabrication of small-sized artificial vessels using a three-dimensional bio-printer. The fabrication employed biodegradable polycaprolactone and autologous MSCs harvested from the bone-marrow of canines. The MSCs were cultured and differentiated into endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…While other researchers like Laura Niklason at Duke (later Yale) ( 285 , 286 ) also started their programs initially on the basis of bioreactor-based vital implants using degradable scaffolds ( 163 ), the group in Montreal went a step further. In an attempt to avoid all synthetic scaffolds and the associated problems of shrinkage and fibrosis, L'Heureux and Auger created polymer-free neo-vessels consisting of adventitial fibroblatsts, medial smooth muscle cells and an endothelium ( 287 291 ) Their extreme modern pendent are 3D printed pure stem-cell grafts ( 292 ). In clinical pilot trials with L'Heureux's AV-shunts graft dilatation was observed ( 288 ).…”
Section: A Protracted Evolutionmentioning
confidence: 99%
“…While other researchers like Laura Niklason at Duke (later Yale) ( 285 , 286 ) also started their programs initially on the basis of bioreactor-based vital implants using degradable scaffolds ( 163 ), the group in Montreal went a step further. In an attempt to avoid all synthetic scaffolds and the associated problems of shrinkage and fibrosis, L'Heureux and Auger created polymer-free neo-vessels consisting of adventitial fibroblatsts, medial smooth muscle cells and an endothelium ( 287 291 ) Their extreme modern pendent are 3D printed pure stem-cell grafts ( 292 ). In clinical pilot trials with L'Heureux's AV-shunts graft dilatation was observed ( 288 ).…”
Section: A Protracted Evolutionmentioning
confidence: 99%
“…6 Data was obtained from parts printed using a Form 2, 100 µm, High Temp settings, and postcured with Form Cure at 80 • C for 120 min. 7 Data was obtained from parts printed using a Form 2, 100 µm, High Temp settings, and postcured with Form Cure at 60 • C for 60 min plus an additional thermal cure in a lab oven at 160 • C for 90 min.…”
Section: Structural Resinmentioning
confidence: 99%
“…3D bioprinted vascular grafts, comprised of autologous mesenchymal stem cells printed onto conventional artificial grafts, were implanted into canine bilateral carotid and femoral arteries. Those that received the bioprinted grafts showed increased endothelialization and decreased inflammation relative to a control group that received artificial grafts alone ( 80 ). Microsteriolithography was utilized to generate an artificial limbus structure using rabbit limbal fibroblasts and endothelial cells.…”
Section: D Bioprinted Tissue and Organ Constructsmentioning
confidence: 99%